Progressive engineering practices in marine resource management - Zlateva, Ivelina, 1976-; Raykov, Violin, 1974-; Nikolov, Nikola, 1960- (Advances in environmental engineering and green technologies (AEEGT) book series., 2015)
"This book combines scientific, ecological, and engineering approaches involved in the sustainable management of natural resources, featuring coverage on key topics relating to environmental management, maritime spatial planning, sustainable fisheries, and waste water treatment"--